Characterizing population pharmacokinetic/pharmacodynamic relationships in pulmonary tuberculosis infected adults using nonlinear mixed effects modelling - Smythe, Wynand Anton (Division of Clinical Pharmacology, 2016)
This pharmacokinetic sub-study was nested within the phase-III OFLOTUB study investigating the shortening of tuberculosis treatment. A total of 343 adults enrolled in Benin, Guinea, Senegal, and South Africa were randomized to receive rifampicin, isoniazid, pyrazinamide, and ethambutol in the standard 6-month control regimen or the 4-month test regimen where gatifloxacin replaced ethambutol. The pharmacokinetics of all drugs was described at first dose and steady-state using nonlinear mixed-effects modelling, and individual exposures were summarised as area under the concentration-time curve (AUC0-24) and peak concentration. Autoinduction of rifampicin metabolism was characterized with a semi-mechanistic enzyme turn-over model. Gatifloxacin dose was evaluated using Monte Carlo simulations. Lastly, Classification & Regression Tree (CART) analysis techniques were used to identify factors predictive of 2-month culture conversion or 24-month long-term composite outcome. Consistent with literature findings, approximately 73.0, 43.0, 0.3, 6.0 and 0.0% of patients failed to achieve previously reported target concentrations for rifampicin, isoniazid, pyrazinamide, ethambutol, and gatifloxacin, respectively.